Astrophysics of the diffuse universe - Dopita M A; Sutherland R S (Berlin Springer-Verlag, 2003)
The book is designed as an astrophysics textbook that provides a comprehensive introduction to the physics of Interstellar Matter. The objective of Astrophysics of the Diffuse Universe is to show how physics can be applied to the understanding and diagno
Keywords: Astrophysics; Interstaller matter